Traffic safety as a factor of improving logistics in construction sector - Slobodan Ognjenovic, Tatiana Sazonova, Riste Ristov, Ivana Nedevska, Anton Kibkalo (MATEC Web of Conferences 73, 07002, 2016)
Security is a complex problem. It includes the driver’s behavior, the features of the vehicle, those of the road and the driving conditions. Security can be approached from the aspect of the vehicle and pavement design, of driving habits, traffic regulation and application of laws. The good coordination of the driver, the vehicle and the road enables for better estimation of the traffic safety relations and interrelations giving the possibilities of improvement of the situation at present and in future. The driver has the main role in the determination of the success or failure of the road system. Over 90% of the accidents are due to improper behavior of people in traffic. Understanding of the human factors is the key factor in the optimal road design and traffic flow. Nevertheless, engineers need more understanding about driving behavior, as they are responsible for road design, for the traffic flow, and for the regulations intended to avoid errors wherever possible. The purpose of this paper is to inform about the current situation both in practice and in the researches of traffic safety, as well as to yield a broader review of the actual traffic safety situation on the roads in Republic of Macedonia.